SISTEM PENYIMPANAN PERALATAN DI STORE ANGKASA GARDEN HOTEL PEKANBARU - Siti Sesyarifah Hendarningtias; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Hotel is a form of accommodation that is managed commercially, provided for everyone to obtain lodging services along with food and drink and others for everyone who stays at the hotel. The storage system is a system that is needed in storing goods for ease of work, storage can be created and the discovery of items that have been stored can be easily found when these items are to be used. Store is a building used to store goods. This study aims to find out how the equipment storage system is at the Angkasa Garden Hotel Pekanbaru store. Angkasa Garden Hotel Pekanbaru is a 3 star hotel founded by PT. Angkasa Megah Kencana which was built on March 12 2011, and started operating on June 10 2012. The method used is a qualitative descriptive method which is a method that focuses more on observation and natural conditions. Keywords: storage system,store,hotel